JUSTIFICATION OF THE METHODOLOGICAL FOUNDATIONS FOR STUDYING THE SELF-CONCEPT OF PERSONALITY AND INCEST TRAUMA - Hlushchenko, Mykyta (PSYCHOLOGICAL JOURNAL, 2025)
This article presents a theoretical and methodological analysis of the principles for studying the self-concept and the impact of incest trauma on the structure of personality. The phenomenon of the self-concept is examined as an integrated system of self-perception. It is established that the cognitive, emotional-evaluative, and behavioral-motivational components constitute interrelated structural elements of the self-concept. The role of incest trauma in transforming personality structure is identified. The specific manifestations of the self-concept in individuals with incest trauma are systematized, along with an indication of the modality of their personality profiles. It is proposed that the configuration of self-concept components be viewed along a continuum ranging from constructive to destructive registers. The destructive (negative) profile of the self-concept in individuals with incest trauma is characterized by low self-esteem, impaired personal boundaries, mistrust of the world, dissociation, hypo- or hypersexualization, and alienation from one’s bodily self. In contrast, the constructive (positive) profile is marked by self-acceptance as a whole person, a positive attitude toward the body, an adequate perception of sexuality, and a healthy assertion of personal boundaries. Based on the conducted theoretical investigations, the article substantiates the relevance and appropriateness of employing a designated set of psychodiagnostic tools for studying the self-concept in individuals affected by incest trauma.